(Al-Kanani 2017; Al-Shahri 2004)Irony and Satire in the Iraqi Novel After 2003 Irony and sarcasm in the post-2003 Iraqi novel - Al-Saadi, Mohammad Ali Hassan Khalaf; Al-Shuwaili, Abdul Moneim Jabbar Obaid (Journal of Posthumanism, 2025)
The research aims to study one of the functions of narration in terms of construction, namely irony and sarcasm, which limits the path of the novelist who takes in writing his narrative text. It shows the description of the frames of the character and the goal to achieve. In addition, it links it to the imaginative ability capable of achieving the goal of the novelist in his text, and as it is known that this function cannot be always interrogated and places, because it goes out for a specific goal to achieve. Then, it may become recognized and does not achieve an aim. In another time, irony and sarcasm can show what is satirical in a serious dress purposeful for a certain purpose. So, the researcher has examined this theme in the Iraqi novels after 2003. Despite the lack of this feature, I found some texts that were characterized by this feature as explained in the texts used in this article.